2010
DOI: 10.1159/000317332
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Tissue Engineering Using Natural Scaffolds in a Porcine Model: Role of Toll-Like Receptors and Impact of Biomimetic Molecules

Abstract: Introduction: Natural scaffolds have been shown to induce T helper 2 (TH2)-specific immune responses in host tissues; however, the precise mechanisms that underlie this immune response are unknown. Using a porcine animal model, we evaluated the role of Toll-like receptors (TLRs) and matrix remodelling in the implantation of bladder acellular matrix (ACM) grafts and ACMs fortified with biomimetic materials. Materials and Methods: Bladders were decellularized with detergent and treated in 3 different ways prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…When these matrixes were treated with hyaluronic acid or vascular endothelium growth factor (VEGF), the lymphocytes migration was reduced and the TGF β-1 production was increased. 10,11 Several cell sources have been used for cell therapy, including adult stem cells, embryonic stem cells, induced pluripotent stem cells, etc. Studies have shown that ADSCs and MDSCs stimulate pro-angiogenic cytokines such as hepatocytic growth factor (HGF), TGF-β, VEGF, fibroblastic growth factor type 2, angiopoietin-1, placenta growth factor, and play an essential part in the antifibrosis effect.…”
Section: Discussionmentioning
confidence: 99%
“…When these matrixes were treated with hyaluronic acid or vascular endothelium growth factor (VEGF), the lymphocytes migration was reduced and the TGF β-1 production was increased. 10,11 Several cell sources have been used for cell therapy, including adult stem cells, embryonic stem cells, induced pluripotent stem cells, etc. Studies have shown that ADSCs and MDSCs stimulate pro-angiogenic cytokines such as hepatocytic growth factor (HGF), TGF-β, VEGF, fibroblastic growth factor type 2, angiopoietin-1, placenta growth factor, and play an essential part in the antifibrosis effect.…”
Section: Discussionmentioning
confidence: 99%
“…After mapping of the gene sequences for human and murine PRRs, exploration of the genomic sequence of other species has allowed the identification of homologs of the majority of TLRs in dogs, cats, cattle, sheep, goats, horses, and pigs . Other PRRs have also been identified in these species, although less is known about them than the TLRs (Table ).…”
Section: Immunopathology Of Sepsismentioning
confidence: 99%
“…It is produced by extracting the cells and soluble matrix components from the extracellular matrix, and so it has almost all the properties of a normal bladder, and maintains a low potential for inflammatory attack on the graft because most of the antigenic proteins are extracted from the bladder tissue. The long-term follow-up of vascular acellular matrix allografts has demonstrated their biocompatibility [3-5]. …”
Section: Introductionmentioning
confidence: 99%